Autism spectrum disorder in a patient with a genomic rearrangement that only involves the EPHA5 gene. (June 2019) - Pascolini, Giulia; Majore, Silvia; Valiante, Michele; Bottillo, Irene; Laino, Luigi; Agolini, Emanuele; Novelli, Antonio; Grammatico, Barbara; Calvani, Mauro; Grammatico, Paola
Abstract : About one child in 68 is affected by the autism spectrum disorder (ASD), one of the most common neurodevelopmental disorders linked to intellectual disability, especially in males, intellectual disability being diagnosable in about 60–70% of autistic individuals. The biological bases of ASD are not yet fully known, but they are generally considered multifactorial, although many genes and genomic loci have been proposed to be possibly associated with this condition. In this report, we describe the case of a 14-year-old female Italian proband affected by ASD, carrying a novel ~ 270 kb interstitial microduplication, localized at the distal portion of the 4q13.1 region. The rearrangement was inherited from a mild symptomatic father and included a large part of the single EPHA5 gene, a receptor tyrosine kinase involved in the neural development, already indicated to be linked to ASD by previous Genome Wide Association Studies. This imbalance represents, to the best of our knowledge, the smallest duplication identified to date that only impacts the EPHA5 gene. We hypothesize that the duplication of this gene may alter EPHA5 expression and that this may impact the autistic phenotype of the patient.